Рекреаційне використання державного історико-культурного заповідника “Тустань” = Recreational use of the State Historical and Cultural Reserve “Tustan” - Kepeniak, Nadiia Mykolaivna (Journal of Education, Health and Sport, 2015)
Kepeniak Nadiia. Рекреаційне використання державного історико-культурного заповідника “Тустань” = Recreational use of the State Historical and Cultural Reserve “Tustan”. Journal of Education, Health and Sport. 2015;5(9):217-226. ISSN 2391-8306. DOI10.5281/zenodo.30533 http://dx.doi.org/10.5281/zenodo.30533 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A217-226 https://pbn.nauka.gov.pl/works/619876 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 29.08.2015. Рекреаційне використання державного історико-культурного заповідника “Тустань” Recreational use of the State Historical and Cultural Reserve “Tustan” Kepeniak Nadiia Надія Кепеняк – аспірантка географічного факультету ЛНУ імені Івана Франка Nadiia Kepeniak, Ivan Franko National University of Lviv, graduate student Ключові слова: рекреація, НПП, Тустань, Урицькі скелі, Сколівські Бескиди. Key words: recreation, NPP, Tustan, Uritsky rocks, Skole Beskids. Анотація. У статті охарактеризовано одну з найважливіших історико- архітектурних пам’яток національного природного парку “Сколівські Бескиди” це – Урицькі скелі. Описано історичне значення фортеці Тустань. Подана інформація що до використання цієї території як осередку проведення фестивалю “Ту Стань!”. На даний час ця територія використовується як рекреаційний об’єкт НПП “Сколівські Бескиди”, тому ми акцентуємо увагу на його туристичну привабливість. Abstract. The article describes one of the most important historical and architectural monuments national park “Skole Beskids” is - Uritsky rocks. We describe the historical significance of the fortress Tustan. Information submitted that the use of this area as the center of the festival “Tu Stan”. Currently, the area is used as a recreational facility NPP “Skole Beskids” because we focus on its tourist appeal.